Thalamic tumours invading the brain stem produce crossed cerebellar diaschisis demonstrated by PET. Issue 5 (May 1986) - Fukuyama, H; Kameyama, M; Harada, K; Fujimoto, N; Kobayashi, A; Taki, W; Ishikawa, T; Handa, H; Tanada, S; Torizuka, K
Abstract : Two cases of thalamic tumour, spreading through the midbrain into the pons ventrolaterally, showed suppression of cerebellar blood flow on the opposite side to the tumour, and also showed reduction of blood flow in the pons on the side of the tumour in positron emission tomographic studies. The pathophysiological mechanism of crossed cerebellar diaschisis may be due to functional suppression of the pontine nuclei by destruction of descending fibres from the cerebral cortex.